Comparison of psychological characteristics (anxiety, depression, stress) of inpatients and outpatients with covid-19 - Daneshnejad, Fareshteh; Shahbazi, Maryam (Applied Family Therapy Journal (AFTJ), 2021)
Aim: The present study compared the psychological characteristics of critically ill and hospitalized patients with outpatients suffering from covid-19. Research method: The statistical population of this research includes all inpatients and outpatients who visited the health centers of Ivan city in the second 6 months of 2020, for whom a definitive diagnosis of Covid-19 disease was given using the PCR test. The sampling method of the present study was available sampling. 200 people (100 people from each group) from people with covid-19 who received inpatient or outpatient services in the health centers of Eyvan city and were confirmed to have the disease based on the PCR diagnostic test, were selected as a statistical sample. DASS-21 anxiety, depression, stress questionnaire was used for measurement and evaluation. Data analysis was done using the t-test of independent groups. Results: The data analysis results showed a significant difference between the level of anxiety, depression and stress of inpatients and outpatients. In this case, hospitalized patients reported a higher level of anxiety, depression and stress. Conclusion: Suppose the psychological aspects effective in the disease while reducing the cases of death and hospitalization cases, considering the possibility of all people in the society being affected by identifying people prone to psychological disorders at different levels of the society, whose mental health may be endangered; The mental health of these people can be maintained through appropriate psychological solutions and techniques. Also, paying attention to the psychological condition of patients while making them resistant to the disturbances caused by the disease can reduce the psychological complications caused by the disease after the long treatment period and the prevalence of mental disorders in the society.